Nitrification suppression and spinach growth in alkaline soil - Riggert, Craig E., author; Moore, Frank D., III, advisor; Basham, Charles W., committee member; Soltanpour, Parviz N., committee member (Colorado State University. Libraries, 1976)
A single at-planting application of (NH4)2SO4 with and without nitrapyrin, [2-chloro-6-(trichloromethyl) pyridine], was evaluated on spinach in alkaline soil in 2 field experiments and 1 greenhouse experiment. Parameters measured were soil NH4 -N and NO3 -N, spinach yield, leaf color and leaf P, Fe and Zn. Nitrapyrin was adsorbed onto (NH4)2SO4 crystals then applied in a band at planting in the field experiments. The first field experiment consisted of N application rates of 87. 8 and 157.5 kg/ha and nitrapyrin rates of 0, 280 and 560 g/ha while the second field experiment included N application rates of 0, 45 and 90 kg/ha and nitrapyrin rates of 0, 140, 280 and 420 g/ha. Nitrapyrin (1.5 ppm - dry soil weight basis) was adsorbed onto (NH4)2SO4 crystals and incorporated with soil in the greenhouse at N rates of 0, 400 and 800 mg/2 kg dry soil. Drainage was prevented in this greenhouse experiment. Spinach yields were measured and leaf and soil samples were taken at harvest from the first field experiment and the greenhouse experiment. Yields were measured and leaf and soil samples were taken 28, 42, 48 and 56 days from planting in the second field experiment. Apparently little leaching occurred in the first field experiment and final yield was greatest when N applications included 280 g nitrapyrin/ha. This resulted in high soil concentrations of both NH4 and NO3 at harvest. Concentrated soil NH4 resulting from prolonged nitrification suppression with as much as 560 g nitrapyrin/ha produced good plant growth on this alkaline soil. Leaching had apparently occurred in the second field experiment and increased yields with nitrapyrin 56 days from planting were attributed to increased soil N retention. Prolonged nitrification suppression from 1.5 ppm nitrapyrin in the greenhouse resulted in severely stunted plant growth along with other NH4 toxicity symptoms. Leaf color, which is important in determining market and nutritional quality of spinach, was darker green when (NH4)2SO4 adsorbed with nitrapyrin was applied. This was measured during all 3 experiments. The dark green leaf color was measured and/or observed well before observed yield differences. Leaf P, Fe and Zn concentrations were generally increased when NH4 applications included nitrapyrin in this study. Leaf P concentrations increased the most while leaf Zn concentrations increased the least. Increase in leaf P, Fe and Zn concentrations due to the addition of small amounts of nitrapyrin to NH4 fertilizer may be an important consideration with regard to alkaline soils where P, Fe and Zn are often limiting.
Covers not scanned.
Keywords: Nitrification; Spinach